Evaluation of the stability and antibacterial activity of crude extracts of hydro-endophytic fungi - Surachai Techaoei; Khemjira Jarmkom; Thisakorn Dumrongphuttidecha; Warachate Khobjai (Wolters Kluwer Medknow Publications, 2021)
The production and screening of secondary metabolites of four hydro-endophytes isolated from lotus, and the stability of bioactive compounds was evaluated. Surface-sterilized technique was used to isolate the endophytic fungi (EF) on potato dextrose agar and identified by using morphological and molecular techniques. The extracts were tested for anti-microbial activity against methicillin-resistant Staphylococcus aureus (MRSA) DMST20651, Streptococcus mutans (SM) DMST18777, Staphylococcus epidermidis (SE) ATCC12228, Pseudomonas aeruginosa (PA) TISTR1467, and Propionibacterium acnes (PN) DMST14916. The bacteriostatic and bactericidal activities were determined. Finally, thermal and ultraviolet (UV) stability was evaluated. Four endophyte isolates (EF 14, EF36, EF53, EF58, and EF60) produced secondary metabolites and showed activity against MRSA, SM, SE, PA, and PN, respectively. The crude ethyl acetate (EtOAc) and methanol (MeOH) extract of EF14 showed activity against MRSA with the inhibition zone of 9.00 ± 0.00 and 7.50 ± 0.50 mm, and minimum inhibitory concentration was 4.80 and 4.90 mg/mL, respectively. The minimum bactericidal concentration was 9.60 mg/mL. Whereas, the crude EtOAc and MeOH extract EF60, which were extracted by EtOAc and MeOH, showed inhibition zone of SE as 12.33 ± 0.57 and 12.33 ± 0.57 mm, respectively. Crude EtOAC extracts of EF14 showed highest thermal stability at 55°C-121°C, and UV stability with MRSA and SE, respectively. The results showed that the EtOAc extracts of EF could be potential antibacterial pathogens and displayed UV-thermal stability. This information is beneficial for future investigations, since some bioactive compounds have potential as anti-resistant strains of some bacterial pathogens.